PEMBELAJARAN BERDASARKAN MASALAH (PROBLEM-BASED LEARNING) PADA MATERI PELUANG KEJADIAN SEDERHANA DI KELAS IX SMP NEGERI 3 TULUNGAGUNG - Katiasri Katiasri (INSPIRASI : JURNAL ILMU-ILMU SOSIAL, 2015)
Problem Based Learning is a learning model that emphasizes student to be active. Students are given a chance to study by themselves for building their knowledge based on self-experience and experiment. The research aims are to 1) compare the average score of student learning outcomes by implementing problem based learning model in group and classical for simple matter opportunities event, and to 2) know whether implementingÂ  problem based learning model in group is effective for teaching simple matter opportunities event in 9th grade of 3rd State Junior High School or not. This research is quasi experimental. The research design is randomized static group comparison design. The conclusion are 1) the average score of student outcomes by implementing problem based learning model in group is higher than classical for simple matter opportunities event in 9th grade of the 3rd State Junior High School, 2) Problem based learning model in group is more effective for teaching matter opportunities event in 9th grade of 3rd Junior High chool.